PENGARUH MOTIVASI, LINGKUNGAN KELUARGA DAN EKSPEKTASI PENDAPATAN TERHADAP MINAT BERWIRAUSAHA (STUDI KASUS PADA MAHASISWA UNIVERSITAS TRIDINANTI PALEMBANG) - Dian Septianti (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study aimed to analyze the influence of motivation, family environment and the expected revenue of the interest in entrepreneurship (a case study in Palembang Tridinanti University students). Data analysis method used is qualitative and quantitative, data sources using primary and secondary in the form of questionnaires, interviews, and documentation. The population in this study were all students at the University Tridinanti Palembang with a sampling technique that acidental sampling with a sample size of 100 respondents specified. The results showed that there is significant influence between motivation, family environment and the expected revenue against the interests of students in entrepreneurship (case study at university students Tridinanti Palembang) simultaneously with Sig. 0,000. Partially also found to influence the motivation, family environment and the expected revenue to be motivational variables that most influence on student interest in entrepreneurship. Key words : Motivation, family environment, Expectation Income, Interests